Strategi Digital Marketing Untuk Meningkatkan Penjualan Tas di E-Commerce - Titin Sumarni; Siti Murasih; M. Iqbal Romadhan; Ayu Suraya (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This research aims to analyze effective digital marketing strategies in increasing sales of bag products on e-commerce platforms. In the digital era, the use of technology and online platforms is the main key for business actors to reach a wider range of consumers. This study identified various digital marketing techniques such as search engine optimization (SEO), marketing via social media, paid advertising (PPC), content marketing, as well as the use of influencer marketing. Additionally, data-driven personalization strategies and consumer behavior analysis are also discussed to improve customer experience and sales conversion. The combination of an attractive content strategy, use of data analytics technology, and consistent interaction with consumers can have a positive impact on sales of bag products on e-commerce platforms. These findings provide guidance for business actors in designing more effective and targeted digital campaigns. This research is descriptive research with a qualitative approach with the research object being digital marketing strategies to increase bag sales in e-commerce. Data types are primary data and secondary data. Primary data is data collected directly by researchers or data practitioners in the field. Meanwhile secondary data is a type of data collected from previously existing data. Data sources will be taken from documents, interview results, and results from observations. By means of private chat/message between the researcher as interviewer and the informant.